2021
DOI: 10.1002/admt.202101126
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Microchannel Encapsulation to Improve the Stretchability of Flexible Electronics

Abstract: Recently, stretchable inorganic electronic devices are rapidly developed, comprising emerging design strategies and fabrication techniques for assembling high‐performance electronic components in slight, soft, and flexible forms, with broad medical and industrial applications. Although reliable encapsulation plays an indispensable role in offering physical and chemical protection for flexible devices, there are relatively few studies on flexible encapsulation, and conventional encapsulation methods still suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…This requires the mechanical robustness of two ‘soft–rigid’ interfaces: (1) rigid functional materials and soft elastomer substrates in skin bioelectronics, and (2) rigid bioelectronic devices and soft biological skin. Strategies such as an additional intermediate layer, 228 surface treatment, 179 heat pressing, 34 cold welding, 152 reinforcement, 237 infiltrating, 238 mixing, 23 and encapsulation 239,240 have been employed to improve the adhesion of the rigid–soft interface during device fabrication, thus enhancing device durability. Generally, through these fabrication techniques, a functional surface composite or homogeneous composite can be obtained.…”
Section: Towards Long-term Continuous Health Monitoringmentioning
confidence: 99%
“…This requires the mechanical robustness of two ‘soft–rigid’ interfaces: (1) rigid functional materials and soft elastomer substrates in skin bioelectronics, and (2) rigid bioelectronic devices and soft biological skin. Strategies such as an additional intermediate layer, 228 surface treatment, 179 heat pressing, 34 cold welding, 152 reinforcement, 237 infiltrating, 238 mixing, 23 and encapsulation 239,240 have been employed to improve the adhesion of the rigid–soft interface during device fabrication, thus enhancing device durability. Generally, through these fabrication techniques, a functional surface composite or homogeneous composite can be obtained.…”
Section: Towards Long-term Continuous Health Monitoringmentioning
confidence: 99%
“…Resembling the lymphatic structure (Figure 1b), the proposed artificial lymphatic system consists of a pump cavity, duckbill valves, ducts for connection and additional wireless flow rate sensors (Figure 1c). All of the compositions are made of soft silica gel, whose modulus is around 20 kPa 39 and similar to that of human tissues, thus can reduce discomfort and avoid severe pain. An external magnetic field was applied to actuate an internal magnetic tablet and enlarge the controllable range of the flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…4C. 77 Through finite element analysis and experimental investigation, the team showed that the stretchability of the electronic device improved significantly.…”
Section: Microfluidic Solutions For Enhanced Stretchability Of On-ski...mentioning
confidence: 99%